Contribution to the taxonomy, distribution and paleoecology of the early representatives of Penthesilenula Rossetti & Martens, 1998 (Crustacea, Ostracoda, Darwinulidae) from Argentina, with the description of a new species - Ballent, Sara Cristina (2012)
Early Mesozoic Argentinian darwinuloids, now re-assigned to the genus Penthesilenula (incae group), are described and illustrated. These records seem to constitute the oldest known for the genus. The close similarities between the studied species and those described from eastern Asia enlarge the geographical distribution of Penthesilenula (incae group), which, although restricted to the southern Hemisphere in Recent and Holocene times, may have had a wider distribution in the past. Additional information on the paleoecology, plus a preliminary account on the distribution of darwinulid species from Argentina are also offered. One new species is described: Penthesilenula loana sp. nov.